The worm has turned: Behavioural drivers of reproductive isolation between cryptic lineages. (July 2016) - Jones, G.L.; Wills, A.; Morgan, A.J.; Thomas, R.J.; Kille, P.; Novo, M.
Abstract: Behavioural processes such as species recognition and mate attraction signals enforce and reinforce the reproductive isolation required for speciation. The earthworm Lumbricus rubellus in the UK is deeply differentiated into two major genetic lineages, 'A' and 'B'. These are often sympatric at certain sites, but it is not known whether they are to some extent reproductively isolated. Behavioural tests were performed, in which individually genotyped worms were able to choose between soils previously worked either by genetically similar or dissimilar individuals (N = 45). We found that individuals (75%) were significantly (P < 0.05) more likely to orientate towards the soil conditioned by worms of their own lineage. Further testing involved a choice design based on filter papers wetted with water extracts of soils worked by a different genotype on each side (N = 18) or extracts from worked soil vs . un-worked control soil (N = 10). Again, earthworms orientated towards the extract from their kindred genotype (P < 0.05). These findings indicate that genotype-specific water-soluble chemicals are released by L. rubellus ; furthermore, they are behaviour-modifying, and play a role in reproductive isolation between sympatric earthworm lineages of cryptic sibling species, through pre-copulatory assortative mate choice. Highlights: Two cryptic lineages live in sympatry and in a similar proportion within studied area. Behavioural tests were performed. Evidence for pre-copulatory sexual selection mechanisms is shown in cryptic lineages. Attraction for individuals of same lineage may be due to specific chemical signals. This attraction is mediated by water-borne molecules.